Planning for Adaptation: A System Approach to Understand the Value Chain's Role in Supporting Smallholder Coffee Farmers' Adaptive Capacity in Peru - Morales, Laura V.; Robiglio, Valentina; Baca, María; Bunn, Christian; Reyes, Martin (Frontiers in Climate, 2022)
Coffee is a major global commodity whose production is sustained by and provides livelihoods for millions of smallholder families in the tropics. However, it is highly sensitive to climate change and the climate risk family farmer’s face from direct impacts on coffee production are often compounded by further impacts on the physical and social landscapes and infrastructure. We examine the vulnerability (sensitivity and adaptive capacity) of smallholder coffee farmers in northeastern Peru via the lens of their central participation in a value chain that mediates access to livelihood assets, affecting their adaptive capacity and aspects of their sensitivity. Using a staged and participatory, mixed-methods approach, we sought to understand the territorial climate exposure, the structure of the regional value chain and role of different actors in supporting farmer adaptive capacity and assess the vulnerability of the entire value chain (including other actors in addition to farmers). We found heterogeneity not only in the potential impact of climate change on coffee production, future adaptation needs and vulnerability of farmers across the territory (among elevational zones and regions), but in the distribution of vulnerability among value chain actors. Farmers are the most vulnerable actors, simultaneously the most sensitive and with the lowest adaptive capacity, issues stemming from their strong territorial dependence and pre-existing social and economic asymmetries with actors in the coffee value chain who are not as territorially dependent (e.g., private companies). We make the case that supporting the adaptation of smallholder farmers in the study region requires moving beyond a value-chain approach to a territorial systems perspective that more intentionally involves those actors with stronger, locally vested interests (e.g., local governments and institutions) in their adaptation and requires the strengthening capacities of these actors in various areas.